2020
DOI: 10.1088/1361-6463/aba068
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally validated computations of simultaneous ion and fast neutral energy and angular distributions in a capacitively coupled plasma reactor

Abstract: Accurate predictions of the ion energy and angular distribution functions (IEADFs) and fast neutral energy and angular distribution functions (FNEADFs), are essential for a range of critical applications in the plasma processing of thin film etching and deposition. Computationally efficient methods that can be applied to industrial reactor systems that are also validated across a range of operating conditions are essential for prediction of IEADFs and FNEADFs. In this work, we present a hybrid model where a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…L for electrons in N 2 with the corresponding values that are determined by Kawaguchi et al [58]. In this figure, n 2 0 D 3L is determined from Monte Carlo simulations by using equation (24), while n 2 0 D α 3 3L is evaluated from the alpha parameters based on equation (25) from reference [58] by neglecting the alpha parameters of fourth and higher order. Kawaguchi and coworkers determined alpha parameters from the arrival time spectra experiment and the Monte Carlo simulations.…”
Section: 32mentioning
confidence: 97%
See 2 more Smart Citations
“…L for electrons in N 2 with the corresponding values that are determined by Kawaguchi et al [58]. In this figure, n 2 0 D 3L is determined from Monte Carlo simulations by using equation (24), while n 2 0 D α 3 3L is evaluated from the alpha parameters based on equation (25) from reference [58] by neglecting the alpha parameters of fourth and higher order. Kawaguchi and coworkers determined alpha parameters from the arrival time spectra experiment and the Monte Carlo simulations.…”
Section: 32mentioning
confidence: 97%
“…The results for the model and the real gases were obtained from the Monte Carlo simulations and numerical multi-term solution of the Boltzmann equation. In particular, it was necessary to follow a large number of electrons (at least 10 7 ) in our Monte Carlo simulations in order to calculate third-order transport coefficients accurately, due to high statistical fluctuations of individual terms appearing in expressions (24) and (25). It was also necessary to determine the phase space distribution function with a high degree of precision in order to calculate the third-order transport coefficients from the multi-term method.…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many computational LTP modeling codes have been developed by groups in academia, 42 the semiconductor industry, 70 and software vendors. 66,71,72 If one examines the capabilities of these plasma modeling tools, it will appear that one can adequately model most plasma processing 64 systems described in Sec. 2, often with the actual processing chemistries under realistic operating conditions.…”
Section: Perspectivementioning
confidence: 99%
“…138) The ion energy and angular distribution functions (IED and IAD) of ions and fast neutrals were estimated computationally by a hybrid model of fluid and particles and they were validated across a range of operating conditions of experiments. 139) The IED were measured by a retarding field energy analyzer and the IED function varies over a pulse period. The results were shown that the ion energy increased and energy spread from single peaked to bi-modal with the decrease of RF power duty cycle.…”
Section: 5mentioning
confidence: 99%